Parental risk perception of mycotoxins and risk reduction behaviour. Issue 6 (27th May 2014) - Niens, Christine; Strack, Micha; Marggraf, Rainer
Abstract : Purpose: – The purpose of this paper is to analyse the parental risk perception of mycotoxins (mould toxins) related to child health in Germany. It ascertains the parental risk reduction behaviour operationalised as parental additional willingness to pay (aWTP) for special child products. It investigates the interrelationships between parental risk perceptions and risk reduction behaviour. Design/methodology/approach: – Altogether, 771 questionnaires were sent to 17 day-care centres in Lower Saxony, Germany. A total of 238 questionnaires were completed. The Perceived Food Risk Index was used to identify the main dimensions of parental risk perception of mycotoxins. Open and closed questions measured aWTP for risk reduction and parental risk estimates. Findings: – The respondents believed that mycotoxins posed a moderate health risk for children in Germany. However, parental risk assessment was found to be subjected to an optimistic bias. Nevertheless, the parents were willing to pay a premium to protect their children's health against mycotoxins. Parental risk perception of mycotoxins could be described by two dimensions named "Dread" and "Control". "Dread" and "Control" predicted aWTP for risk reduction as well as being involved in the genesis of optimistic bias. Research limitations/implications: – Information regarding mycotoxins provided in the questionnaire probably influenced parental responses. This limits the generalisation of the findings. Originality/value: – This research provides initial findings regarding parental risk perceptions of mycotoxins and its impact on risk reduction behaviour. The results are useful for the development of effective risk management and thus for the protection of child health.